Biophysical studies on HCV 1a NS3/4A protease and its catalytic triad in wild type and mutants by the in silico approach - Palanisamy, Navaneethan; Lennerstrand, Johan (Interdisciplinary sciences. Computational life sciences, 2018)
The hepatitis C virus (HCV), of the family flaviviridae, is one of the major causes of chronic liver diseases. Until the year 2012, HCV infections were treated using PEG-interferon and ribavirin combinations, which have a low cure rate and severe side effects. Currently, many direct-acting antivirals (DAAs) are available, e.g. protease inhibitors, NS5A and polymerase inhibitors. These drugs have proven to be efficient in interferon-free treatment combinations and capable of enhancing the cure rate to above 90 %. Unlike PEG-interferon and ribavirin combinations, DAAs select for resistance in HCV. The R155K mutation in the HCV was found to resist all the currently available protease inhibitors. Here, we studied biophysical parameters like pocket (cavity) geometries and stabilizing residues of HCV 1a NS3/4A protease in wild type and mutants. We also studied HCV 1a NS3/4A protease’s catalytic residues: their accessibility, energy, flexibility and binding to Phase II oral protease inhibitor vedroprevir (GS-9451), and compared these parameters between wild type and mutant(s). All these studies were performed using various bioinformatics tools (e.g. Swiss-PdbViewer and Schrödinger’s Maestro) and web servers (e.g. DoGSiteScorer, SRide, ASA-View, WHAT IF, elNémo, CABS-flex, PatchDock and PLIP). From our study, we found that introduction of R155K, A156T or D168A mutation to wild-type NS3/4A protease increases the pocket’s volume, surface (in the R155K mutant, surface decreases), lipo surface and depth and decreases the number of stabilizing residues. Additionally, differences in catalytic residues’ solvent accessibility, energy, root-mean-square deviation (RMSD) and flexibility between wild type and mutants might explain changes in the protease activity and the resistance to protease inhibitors.
Published online: 16 June 2016
Gesehen am 03.03.2020